Death to Smoochy [videorecording (DVD)] - DeVito, Danny; Williams, Robin, 1951-2014; Norton, Edward; Keener, Catherine; Stewart, Jon, 1962-; Fierstein, Harvey, 1952- (Archive collection., 2015)
Former kid-show host Rainbow Randolph hates his squeaky-clean replacement, Sheldon Mopes, a.k.a. Smoochy the Rhino. Randolph is insanely obsessed with getting his job back, but Smoochy's a smash, and their war for kid-vid supremacy places a jaded "KidNet" producer in the middle of a Rainbow/Rhino smackdown.